2011
DOI: 10.1523/jneurosci.2986-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Impaired β-Amyloid Secretion in Alzheimer's Disease Pathogenesis

Abstract: A central question in Alzheimer’s disease (AD) research is what role β-amyloid peptide (Aβ) plays in synaptic dysfunction. Synaptic activity increases Aβ secretion, potentially inhibiting synapses, but also decreases intraneuronal Aβ, protecting synapses. We now show that levels of secreted Aβ fall with time in culture in neurons of AD-transgenic mice, but not wild-type neurons. Moreover, the ability of synaptic activity to elevate secreted Aβ and reduce intraneuronal Aβ becomes impaired in AD-transgenic but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Our findings demonstrate that, under normal conditions, intracellular Aβ (including Aβ 42 and Aβ 40 ) is mainly associated with cytosolic structures and, to a large extent, is secreted from the cells. They may also suggest that deficits in secretion or lysosomal processing would result in intracellular Aβ accumulation and its translocation to the cellular organelles, as seen in AD and its models [12,21,52,53]. Our finding may contribute to better understanding of AD pathogenesis, and may help develop new therapeutic strategies against AD (reviewed in [54]).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our findings demonstrate that, under normal conditions, intracellular Aβ (including Aβ 42 and Aβ 40 ) is mainly associated with cytosolic structures and, to a large extent, is secreted from the cells. They may also suggest that deficits in secretion or lysosomal processing would result in intracellular Aβ accumulation and its translocation to the cellular organelles, as seen in AD and its models [12,21,52,53]. Our finding may contribute to better understanding of AD pathogenesis, and may help develop new therapeutic strategies against AD (reviewed in [54]).…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported recently that Aβ –related synapse damage and memory impairment in AD-transgenic mice correlated with intracellular levels of Aβ but not with plaque burden [20]. Moreover, cultured neurons from AD-transgenic mice showed reduced secretion and enhanced intracellular accumulation of Aβ [21]. Much evidence supports that the lysosomal system, a vacuolar compartment with acidic pH (3.5-6.0), is associated with Aβ generation and neurotoxicity [22-26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this work AD-like synapse damage tracked with intraneuronal Aβ and not at all with plaques. Remarkably, more recent data showed that neurons derived from APP mutant transgenic mice, but not wild type mice, showed declines in Aβ secretion with time in culture, concomitant with a build-up of intraneuronal Aβ (Tampellini et al, 2011). The declining levels of extracellular Aβ in brains of APP mutant mice with aging assayed by in vivo microdialysis (Hong et al, 2011) could support such declining secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Similar age-associated reduction in eAß 1−x level was demonstrated in hAPP mice (Hong et al, 2011). Since eAß 1−x levels are closely related to synaptic activity its reduction in older APP SW and in four month old APP SW /PS1 L166P mice, that represent a more rapidly progressing model of Aß pathology can be interpreted as reduced ability of synapses to secret Aß to the ISF, which evidence was recently provided from studies on primary neuronal cultures derived from Tg2576 mice (Tampellini et al, 2011). …”
Section: Discussionmentioning
confidence: 99%